TINJAUAN HUKUM TERHADAP PENGATURAN PENANAMAN MODAL ASING PADA SEKTOR E-COMMERCE DI INDONESIA: Legal Review of Foreign Investment Regulations in the E-Commerce Sector in Indonesia - Sumaragatha, I Gusti Bagus Sakah; Evangelista, Beverly (Ganec Swara, 2025)
The e-commerce sector in Indonesia is experiencing rapid growth, and regulations regarding foreign investment in this field remain a significant topic of debate in the context of investment law in this country. This study aims to determine the provisions related to foreign investment in the e-commerce sector in Indonesia. It uses a normative research method with a conceptual and legislative approach. The results of the study show that foreign investment regulations in the e-commerce sector in Indonesia have undergone a significant transformation from a strict restriction system through the Negative Investment List (DNI) to a more open and flexible system through the Investment Priority List (DPI).